Restoration of reputation through crisis communication in fashion industry - Vuković Milovan; Dašić Dejan; Vuković Aleksandra (Tekstilna industrija)
The recent wave of crises caused by various factors, which began in 2020, affects all aspects of society, including economic activities. Many industries, including the fashion industry, are experiencing a number of unfavorable developments, chief among them being the reduction in demand for particular goods, damaged reputation etc. Business operations in the conditions of an economic crisis have forced many fashion industry companies to seek adequate mechanisms to face the consequences of this type of crisis. One potential solution to lessen the negative consequences of these occurrences is to implement crisis management in a firm in a systematic way. Crisis communication helps in crisis management, according to a review of businesses' experiences dealing with such an undesirable occurrence or a sequence of events. The subject of this paper is the role of crisis communication in crisis management, particularly from the perspective of companies that dominate the fashion industry. The first part of the paper addresses the various types of crises that all manufacturing companies must consider. The crisis management process, which includes an analysis of potential communication strategies, will be the central focus of the discussion. The final part of the paper examines the operation of companies under high-risk conditions.